PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMAN 1 KUANTAN HILIR - Zikra, Faira Medina (Eko dan Bisnis: Riau Economic and Business Review, 2022)
Based on the results of the analysis of this study, it can be stated that the results of testing the Principal Leadership variable (X) through the t-test can be seen that tcount is greater than ttable (7.105 > 2.01063). Thus, it can be concluded that the Principal's Leadership variable (X) has a positive and significant effect on Teacher Performance at SMAN 1 Kuantan Hiliru. The results of simple linear regression show Y=a+bX, namely: Y= 17.940+ 0.600X. From these equations it can be concluded that the regression coefficient of bx is positive. The result of the R Squere is 0.513 (51.3%), namely the Teacher Performance of SMAN 1 Kuantan Hiliru is influenced by the Principal's Leadership by 51.3% while the remaining 48.7% is influenced by other variables not examined